Analysis of Mathematical Communication Skills in Trigonometry Topic Based on Habits of Mind - Laila Maghfiroh; Mardiyana Mardiyana; Diari Indriati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Mathematical communication is an important skill that must be developed in trigonometry learning but is often not developed optimally. Students tend to rely on procedural formulas without being able to explain, represent, and systematically justify their reasons.  Habits of mind are one of the internal factors indicated to influence students' mathematical communication skills. The purpose of the study to describe students’ mathematical communication skills in trigonometry based on habits of mind. This research uses descriptive approach and qualitative data collection techniques such as mathematical communication skill test and in-depth interviews. The subjects of the study were 22 students of class X E3 at MA Negeri Sukoharjo selected purposively based on their habits of mind categories which are limited, developer and expert, from the results of using the Habits of Mind questionnaire. The result showed that: (1) student with the limited habits of mind category had weak mathematical communication skills in all indicators namely drawing, mathematical expression, and writing; (2) student with the developer habits of mind category showed better mathematical communication skills, but still showed inconsistencies and incompleteness in written representations and narratives; (3) Student in the expert category have excellent mathematical communication skills across all indicators, can communicate mathematical ideas completely, accurately, and systematically. The findings of this study indicate that habits of mind have an important role in developing students’ mathematical communication skills in trigonometry topic. Therefore, teachers are encouraged to design learning activities that encourage habits of mind to improve students' ability to communicate mathematical ideas effectively.